Facile preparation of a novel composite Co-Ni(OH)2/ carbon sphere for high-performance supercapacitors. (21st March 2019) - Jiang, Xinyu; Cheng, Wenbo; Hu, Huijie; Hu, Yiming; Cao, Yunpeng; Yan, Shengnan; Di, Ruixin; Wang, Xiaoze; Hou, Li
ABSTRACT: As an excellent electrode material for supercapacitors, it should have high capacitance like transition metal oxides and good stability like carbon materials. In this work, we reported a novel composite electrode material, Co-Ni(OH)2 /carbon sphere, obtained by a solvothermal method. At first, the activated carbon spheres with an uniform size of about 4µm were synthesized, and then the sheet-like Co-Ni(OH)2 adsorbed on the cracks and outer surface of the carbon spheres to form the Co-Ni(OH)2 /carbon sphere composite. The influence of mass ratio of Co-Ni(OH)2 to carbon spheres on capacitance performance was investigated. Benefitting from the unique composite structure, the synthesized Co-Ni(OH)2 /carbon sphere presents a high specific capacitance up to 959.7 F/g in 6 M KOH at current density of 1 A/g. Meanwhile, the capacitance retention maintains its 75% after 3000 cycles, which is about 2.8 times higher than that of the pure Co-Ni(OH)2, indicating a good stability.